Synthesis and properties of porphyrin nanotubes - Haver, R (2018)
Porphyrins, with their planar aromatic cores, are suitable and versatile building blocks to form functional nanostructures. This thesis describes the synthesis and properties of atomically precise porphyrin nanostructures with a specific focus on porphyrin nanotubes. Chapter 1 introduces the key properties of porphyrins and discusses the template-directed synthesis of (conjugated) porphyrin nanostructures. Furthermore, it explores the "bottom up" synthesis of carbon nanotubes and its molecular analogues including those constructed from porphyrin building blocks. Chapter 2 describes the assembly of a nested nanoring complex. Excitation energy is transferred from the inner nanoring to the outer nanoring. The inner porphyrin nanoring is used as a template to direct the synthesis of the outer nanoring from its linear precursor. Chapter 3 explores different strategies for the synthesis of a nanotube consisting of 12 porphyrin subunits. An unprecedented method of ring-stacking of pre-formed 6-porphyrin nanorings is discussed as well as a template-directed procedure. Chapter 4 describes the host-guest chemistry of a 12-porphyrin nanotube. C60 and C70 fullerenes are encapsulated in the cavity of the nanotube. Electron transfer from the nanotube host to the C60 guest is observed. The guests can be released when the molecular box is chemically opened. Chapter 5 describes the synthesis and properties of porphyrin nanotubes with a mono acetylene connection between the conjoined 6-porphyrin nanorings. This link enables the synthesis of an 18-porphyrin nanotube; the longest p-conjugated molecular nanotube to date. Enhanced conjugation is found compared to analogous bis-acetylene linked tubes. Chapter 6 explores DFT calculations on large p-conjugated porphyrin nanostructures. Size dependent bandgap oscillations in bis-acetylene linked porphyrin nanotubes are examined. TD-DFT studies on a 14-porphyrin nanoball provide insight into the electronic structure and agree with experimental observations.